Targeting transthyretin: mechanism-based treatment approaches and future perspectives in hereditary amyloidosis - Dohrn, Maike F.; Ihne, Sandra; Hegenbart, Ute; Medina, Jessica; Züchner, Stephan L.; Coelho, Teresa; Hahn, Katrin (Journal of neurochemistry, 2021)
The liver-derived, circulating transport protein transthyretin (TTR) is the cause of systemic hereditary (ATTRv) and wild-type (ATTRwt) amyloidosis. TTR stabilization and knockdown are approved therapies to mitigate the otherwise lethal disease course. To date, the variety in phenotypic penetrance is not fully understood. This systematic review summarizes the current literature on TTR pathophysiology with its therapeutic implications. Tetramer dissociation is the rate-limiting step of amyloidogenesis. Besides destabilizing TTR mutations, other genetic (RBP4, APCS, AR, ATX2, C1q, C3) and external (extracellular matrix, Schwann cell interaction) factors influence the type of onset and organ tropism. The approved small molecule tafamidis stabilizes the tetramer and significantly decelerates the clinical course. By sequence-specific mRNA knockdown, the approved small interfering RNA (siRNA) patisiran and antisense oligonucleotide (ASO) inotersen both significantly reduce plasma TTR levels and improve neuropathy and quality of life compared to placebo. With enhanced hepatic targeting capabilities, GalNac-conjugated siRNA and ASOs have recently entered phase III clinical trials. Bivalent TTR stabilizers occupy both binding groves in vitro, but have not been tested in trials so far. Tolcapone is another stabilizer with the potential to cross the blood-brain barrier, but its half-life is short and liver failure a potential side effect. Amyloid-directed antibodies and substances like doxycycline aim at reducing the amyloid load, however, none of the yet developed antibodies has successfully passed clinical trials. ATTR-amyloidosis has become a model disease for pathophysiology-based treatment. Further understanding of disease mechanisms will help to overcome the remaining limitations, including application burden, side effects, and blood-brain barrier permeability.